Hydrodynamic and morphologic effects on the benthic invertebrate ecology along a meander bend of a large river (Paraguay River, Argentina-Paraguay) - Blettler, Martin Cesar Maria (2012)
A detailed hydro-ecological study to identify the effects of bed flow and morphodynamic processes on the distribution (and composition) of benthic invertebrates in a large river is presented herein. A crossing-pool sequence in a meander bend of the Paraguay River (Paraguay-Argentina) was examined. According to the results, there is a link between the benthic fauna, hydraulic and bed sediment size along the bend. The meander pool, with a deep scour hole and the largest bed shear stresses, would be a hostile area for benthic invertebrates, since lower densities were found there. A transversal analysis revealed two different invertebrate assemblages at each of the sampled cross sections: one across the mobile bottom with higher densities but lower diversity, richness and evenness than the other one found close to the banks. On the other hand, a comparison between both Paraguay and Paraná rivers revealed that the first one would seem to have optimal hydraulic conditions for the invertebrate's development, because the hydraulic energy of the Paraná River was too intense for the favorable settlement of benthic organisms at some specific habitats. The overall conclusion of this paper, that morpho-hydraulic features and biotopes are related, is an important step forward in river ecohydrology. With further development of this concept, river management techniques can improve and river rehabilitation projects can be designed with greater confidence.